Cars and Cottages: The Automotive Transformation of Ontario's Summer Home Tradition - Stevens, Peter (Ontario History)

(untitled) (The Ontario Historical Society, 2008)
Automobiles and summer cottages both play important roles in Ontario society, but neither of them has received much attention from scholars. This article examines how the automobile reshaped and reoriented the practice of summer cottaging. Particularly following the Second World War, the automobile served to expand cottaging both socially and geographically. Highway construction opened up new parts of the province to cottage development, while the advantages of automobile travel helped to transform cottaging from an elite activity into a mass phenomenon. Cars changed the nature of cottage life, making it more private and informal. They also led to a striking reversal in government policies, which historically had catered as much to Americans as to Ontarians. Finally the automobile influenced many aspects of cottage country, from its social atmosphere to its natural environment and its political disputes. Ultimately, the car democratized cottaging and, at the same time, fashioned some of the less pleasant features of cottage life.